2001
DOI: 10.2323/jgam.47.321
|View full text |Cite
|
Sign up to set email alerts
|

Presence of several cellulose-binding proteins in culture supernatant and cell lysate of Eubacterium cellulosolvens 5.

Abstract: Attempts were made to separate and characterize cellulose-binding proteins (CBPs) from both the culture supernatant and cell lysate of Eubacterium cellulosolvens 5. Once the CBPs were bound to Avicel cellulose, they were then effectively eluted with the solution containing 3.2 or 5% sodium dodecyl sulfate (SDS), but not eluted with the solution containing various kinds of carbohydrates and reagents. Namely, CBPs in both the culture supernatant and cell lysate of the bacterium bound tightly and strongly to cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…E. coli TOP 10 cells (Invitrogen) were used as a host for recombinants made with TOPO TA cloning (Invitrogen) and the pBAD TOPO TA cloning (Invitrogen). Media and culture conditions were described in previous reports (Toyoda and Minato, 2002a, b;Toyoda et al, 2001Toyoda et al, , 2003.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…E. coli TOP 10 cells (Invitrogen) were used as a host for recombinants made with TOPO TA cloning (Invitrogen) and the pBAD TOPO TA cloning (Invitrogen). Media and culture conditions were described in previous reports (Toyoda and Minato, 2002a, b;Toyoda et al, 2001Toyoda et al, , 2003.…”
Section: Methodsmentioning
confidence: 99%
“…The binding ability of each recombinant protein to cellulose and cell wall fragments was assayed according to the method described in a previous report (Toyoda et al, 2001), with some modifications. The recombinant protein was partially purified by Ni 2ϩ affinity chromatography from the supernatant of E. coli whole-cell lysate.…”
Section: Binding Assay Of Each Recombinant Protein To Cellulose and Cmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] In previous studies, we identified several proteins bound to crystalline cellulose from E. cellulosolvens 5, 5) and cloned and sequenced the gene encoding CBPA and CBPB. 6,7) CBPA and CBPB comprise the catalytic modules of GHF9, two linkers, family 3 carbohydrate-binding modules (CBM3), novel cellulose-binding modules (CBM), and novel cell-wall binding modules.…”
mentioning
confidence: 99%